2020
DOI: 10.1155/2020/9353120
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Politician’s Supporters’ Network on Twitter Using Social Network Analysis and Semantic Analysis

Abstract: Politics is one of the hottest and most commonly mentioned and viewed topics on social media networks nowadays. Microblogging platforms like Twitter and Weibo are widely used by many politicians who have a huge number of followers and supporters on those platforms. It is essential to study the supporters’ network of political leaders because it can help in decision making when predicting their political futures. This study focuses on the supporters’ network of three famous political leaders of Pakistan, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The tweeting behaviour of politicians was generally in line with the results of previous studies (Graham et al, 2013;Larsson and Moe, 2014;Khan et al, 2020). However, out of 14, six (Condemning terrorism acts and/or country's situation/ link with country's safety, Own position, Religious, Energizing party workers, targeting youth and Political report/Highlighting efforts for developments) categories were introduced due to the dominance of content.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The tweeting behaviour of politicians was generally in line with the results of previous studies (Graham et al, 2013;Larsson and Moe, 2014;Khan et al, 2020). However, out of 14, six (Condemning terrorism acts and/or country's situation/ link with country's safety, Own position, Religious, Energizing party workers, targeting youth and Political report/Highlighting efforts for developments) categories were introduced due to the dominance of content.…”
Section: Discussionsupporting
confidence: 86%
“…It is interesting to note that the winning party's account was more active, Tweeted more and retweeted than the opposing parties' accounts. Previous studies also evidenced that there is a significant relationship between increased tweeting behaviour and their winning position (Ahmed, Jaidka and Cho, 2016;Khan et al, 2020). In contrast (Bright et al, 2020) researchers found Twitter campaigns did not impact election outcomes during the 2015 and 2017 UK elections.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As of October 2020, Twitter had over 300 million users worldwide; 91% of them are over the age of 18. is platform attracts many politicians and enables them to interact and use it as a tool in their campaigns [4]. Offering an API that allows extracting public tweets and user's public information and interconnections, it is considered a treasure for researchers aiming for election predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have analyzed and predicted different countries' elections on different social media platforms such as Facebook and Twitter [4][5][6][7][8]. Few studies surveyed this topic [9][10][11].…”
Section: Introductionmentioning
confidence: 99%